SOCIALIZATION OF RFID-BASED SMART LOCK DOOR SYSTEM USING ESP32 AS A SECURITY SOLUTION IN THE LABORATORY ROOM OF SMAN 1 TAJURHALANG - Brajamusti, Jati Kinsela; Pramuaji, Haikal Ilhamullah; Yasa, Aryaguna Abi Rafdi; Yansa, Ryanza Aufa; Riziq, Maulana Ridhwan; Ahmad Hidayatullah; Sugeng Prayitno (Indonesian Journal of Electrical Engineering and Electronics, 2024)
The importance of security technology in educational environments has led to the implementation of an RFID-based Smart Lock Door system with ESP32 at SMAN 1 Tajurhalang. Socialization and education are key to ensuring effective understanding and application by students and staff. Interactive socialization activities and in-depth education about this system aim to increase awareness and understanding of extracurricular room security. The results showed a significant increase in participants’ familiarity and knowledge, from 48% to 91.21%, after training. This increase demonstrates the effectiveness of socialization in changing attitudes and behaviors related to security in extracurricular spaces, creating a safe and conducive learning environment.